Thinking critically about the next decade of convict criminology - Ross, Jeffrey Ian (2024)
Convict Criminology (CC) is a quarter-century old. During those years, this combined approach, group, organization, school, theory, and network has produced scholarly literature and mentored actual and aspiring doctoral students who have been incarcerated and released from carceral custody, assisting them in their careers and engaging in corrections-related policy debates and activism. As the academic fi elds and real-world practice of Corrections and Critical Criminology have changed, and the people who have been involved in CC have come and gone, Convict Criminology has evolved. This paper briefl y reviews the aims and history of CC, then applies a strength, weaknesses, opportunities, and threats (SWOT) analysis to Convict Criminology with the goal of suggesting ways that the leadership, members, and allies of the CC approach might best further its mission.